A photothermally responsive nanoprobe for bioimaging based on Edman degradation. Issue 20 (5th May 2016) - Liu, Yi; Wang, Zhantong; Zhang, Huimin; Lang, Lixin; Ma, Ying; He, Qianjun; Lu, Nan; Huang, Peng; Liu, Yijing; Song, Jibin; Liu, Zhibo; Gao, Shi; et al.
Abstract : A new type of photothermally responsive nanoprobe based on Edman degradation has been synthesized and characterized. Abstract : A new type of photothermally responsive nanoprobe based on Edman degradation has been synthesized and characterized. Under irradiation by an 808 nm laser, the heat generated by the gold nanorod core breaks the thiocarbamide structure and releases the fluorescent dye Cy5.5 with increased near-infrared (NIR) fluorescence under mild acidic conditions. This RGD modified nanoprobe is capable of fluorescence imaging of αν β3 over-expressing U87MG cells in vitro and in vivo . This Edman degradation-based nanoprobe provides a novel strategy to design activatable probes for biomedical imaging and drug/gene delivery.